The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1093/hmg/9.9.1351
|View full text |Cite
|
Sign up to set email alerts
|

KRIT1 is mutated in hyperkeratotic cutaneous capillary-venous malformation associated with cerebral capillary malformation

Abstract: Hyperkeratotic capillary-venous malformations (HCCVMs) are rare cutaneous lesions that occur in a small subgroup of patients with cerebral capillary malformation (CCM). CCMs cause neurological problems that range from headaches to life-threatening intracranial bleeding. CCMs and HCCVMs have a similar histopathological appearance of dilated capillary-venous channels. Genetic linkage of inherited CCMs has been established to three chromosomal loci, 3q25. 2-27, 7p13-15 and 7q21-22. The first mutations were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 19 publications
1
80
0
2
Order By: Relevance
“…No gross lesions were observed on cursory examination of the other internal organs. Because cutaneous vascular lesions have been reported in some human CCM patients, 3 we flayed several Ccm1 ϩ/Ϫ Trp53 Ϫ/Ϫ animals and examined the underside of the skin. No vascular lesions were visible.…”
Section: Identification Of Vascular Lesions In Ccm1mentioning
confidence: 99%
See 1 more Smart Citation
“…No gross lesions were observed on cursory examination of the other internal organs. Because cutaneous vascular lesions have been reported in some human CCM patients, 3 we flayed several Ccm1 ϩ/Ϫ Trp53 Ϫ/Ϫ animals and examined the underside of the skin. No vascular lesions were visible.…”
Section: Identification Of Vascular Lesions In Ccm1mentioning
confidence: 99%
“…Cavernous malformations can form in any part of the central nervous system, and some patients with CCM also have cutaneous vascular malformations. 3 Hemorrhaging of the vessels in a cavernous malformation can result in headaches, seizures, and stroke, that are sometimes lethal.…”
mentioning
confidence: 99%
“…Familial CCMs are inherited in an autosomal dominant pattern, constitute up to 50% of CCM cases, and have been found to be associated with loss-of-function mutations in 3 genes, KRIT1 (also known as CCM1) (1)(2)(3), CCM2 (MALCAVERNIN, OSM) (4,5), and PDCD10 (CCM3) (6,7). Genetic studies in zebrafish have demonstrated that loss of ccm1, ccm2, or the transmembrane receptor heart of glass (heg) results in embryonic cardiovascular phenotypes characterized by a large, thin-walled heart and defective branchial arch artery development that prevents blood circulation (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…This dearth of molecular details is striking, considering the growing list of germline mutations in genes causing specific inherited syndromes involving vascular malformations, including hereditary hemorrhagic telangiectasia (4,5), cutaneous venous malformations (6), cerebral cavernous malformations (7,8), and hyperkeratotic cutaneous capillary-venous malformation (9). Are we able to investigate hemangioma in a similar manner?…”
mentioning
confidence: 99%